Board of Director Diversity and Firm Financial Performance - Erhardt, Niclas L.; Werbel, James D.; Shrader, Charles B. (Corporate governance : an international review, 2003)
This study examines the relationship between demographic diversity on boards of directors with firm financial performance. This relationship is examined using 1993 and 1998 financial performance data (return on asset and investment) and the percentage of women and minorities on boards of directors for 127 large US companies. Correlation and regression analyses indicate board diversity is positively associated with these financial indicators of firm performance. Implications for both strategic human resource management and future research are discussed.